The Effect of Workload and Salary on Turnover Intention At PT. Budi Satria Wahana Motor - Limas, Chandra; Dunan, Hendri (LPPPIPublishing, 2025)
This study aims to analyze the effect of workload and salary on turnover intention among employees at PT. Budi Satria Wahana Motor. Turnover intention reflects an employee's desire to leave the company, which may harm organizational performance and stability. This quantitative study employed multiple linear regression analysis. The entire population of 63 employees was used as the sample through saturated sampling. Data were collected using a Likert-scale questionnaire. The results show that workload has a positive and significant effect on turnover intention, while salary has a negative and significant effect. Simultaneously, both variables significantly influence turnover intention. These findings highlight the importance of balanced workload management and fair compensation systems to reduce turnover intention and improve employee retention.